Penerapan Metode Pembelajaran Survey, Question, Read, Recite, Review (Sq3r) untuk Meningkatkan Keterampilan Membaca Pemahaman - Wahyu Indri Lestari; Chairiyah; Indarwati (Program Studi Pendidikan Profesi Guru, Universitas Sarjanawiyata Tamansiswa Yogyakarta, Indonesia., 2021)
The purpose of this research are: to describe the results of the application of the Survey, Question, Read, Recite, Review (SQ3R) method which can improve reading comprehension skills in third grade students of SD Negeri 1 Cangkreplor for the 2020/2021 school year. This type of research is classroom action research (CAR) which is carried out in two cycles. Each cycle consists of four stages, namely planning, implementing actions, observing, and reflecting. The subjects of this study were the third grade students of SD Negeri 1 Cangkreplor, totaling 28 students. Data collection techniques using test, interview, observation and documentation techniques. Inter-cycle reading comprehension skills increased from the initial condition (pre-cycle) which was 35.7% to 53.6% in the first cycle and then to 89.3% in the second cycle.The conclusion of this study is that the application of the SQ3R learning method can increase the value of reading comprehension skills in third grade students of SD Negeri 1 Cangkreplor Purworejo 2020/2021.